High Fermentable Oligosaccharides, Disaccharides, Monosaccharides, and Polyols (FODMAP) Consumption Among Endurance Athletes and Relationship to Gastrointestinal Symptoms - Killian, Lauren A.; Muir, Jane G.; Barrett, Jacqueline S.; Burd, Nicholas A.; Lee, Soo-Yeun (Frontiers in Nutrition, 2021)
Endurance athletes commonly experience lower gastrointestinal (GI) symptoms similar to those of irritable bowel syndrome (IBS). Previous research on the restriction of fermentable oligosaccharides, disaccharides, monosaccharides, and polyols (FODMAP), a diet-based mitigation strategy initially developed for IBS, has shown promise for application in athlete populations. Athlete’s dietary strategies surrounding exercise have not been formally assessed in relation to FODMAP content of foods or sports nutrition products. Additionally, the FODMAP content of athlete’s habitual diets has not been examined in larger sample sizes. This research aims to investigate the FODMAP content of endurance athlete diets by examining these three areas, in conjunction with GI symptoms. Dietary habits surrounding exercise and GI symptoms were examined in 430 endurance athletes using a previously validated Endurance Athlete Questionnaire. A subset of athletes (n=73) completed a FODMAP-specific food frequency questionnaire for habitual intake. The most commonly reported sports nutrition products were analyzed for FODMAP content using standardized analytical methods. Mean habitual intakes were compared to previous FODMAP studies and medians were compared between those with and without lower GI symptoms. Athletes commonly consumed high FODMAP foods during pre-race dinners and breakfasts, with over 60% reporting specific high FODMAP foods. More frequent nutrition product use, particularly solid, gel/gummy, and homemade products, was often related to increased frequency of GI symptoms. Of the sixteen commonly used sports nutrition products tested, seven were high FODMAP in one serving. All but one of the remaining products became high FODMAP when consumed in multiple servings, as is likely the case during endurance exercise. Average habitual FODMAP intake was 26.1g (±15.9g), similar to intakes classified as high FODMAP in previous research on FODMAPs and IBS or GI symptoms. Only 15.1% of athletes consumed a diet that would be considered low in FODMAP. Exploratory analyses showed higher intake of some FODMAP types among athletes exhibiting various lower GI symptoms. Overall, this study demonstrated that FODMAP intake by endurance athletes is high both surrounding exercise and habitually, and may be contributing to GI symptoms experienced during exercise. This information can be utilized when analyzing athlete diets and selecting foods to decrease GI symptoms.